User experience and user interface: important parameters for an effective design - Ramírez-Acosta, Keren (2017)
It is common to confuse the concepts of user interface and user experience when the topic is not well known. Although both concepts must be equally considered, the designers tend to focus on an aesthetically pleasant interface, which might downplay the experience.The aim of this article is to explain the parameters to be taken into account before and during the design and development of an interface for a software tool. It will also explore the role of the user experience for success in obtaining a usable tool.